Regular cannabis use is associated with history of childhood and lifetime trauma in a non-clinical community sample. (March 2023) - Bassir Nia, Anahita; Weleff, Jeremy; Fogelman, Nia; Nourbakhsh, Sormeh; Sinha, Rajita
Abstract: Higher rate of substance use, including cannabis, has been reported in individuals with a history of childhood trauma, but less is known about the association between cannabis use with lifetime history of trauma and chronic stress, and potential gender differences in this association. This study systematically examined this association in a cross-sectional study of 841 individuals recruited between 2007 and 2012 from the community in New Haven, Connecticut. The Cumulative Adversity Index (CAI) was used to measure cumulative lifetime major life events, life trauma, and recent life events and chronic stress. Childhood Trauma Questionnaire (CTQ) was used to measure childhood trauma. Current and regular use of drugs were assessed using self-report questionnaires and objectively verified with urine drug testing. Higher rates of childhood trauma as well as lifetime trauma, and major life events were found in cannabis users, compared to non-users. The association between cannabis use with childhood trauma (total CTQ scores) was significant after controlling for age, gender, ethnicity and regular use of alcohol or cocaine. In logistic regression analysis, cannabis use had a significant positive association with major life events and lifetime trauma, but not with chronic stress, controlling for confounding factors including age, gender, ethnicity, and regular use of alcohol and cocaine. When analyzed separately, only in women the association between cannabis use and childhood trauma was significant. These associations point to further assessment of the impact of these gender differences on neurobiology of stress and cannabis misuse risk. Highlights: Childhood trauma was positively associated with cannabis use in women. Lifetime cumulative adversity was positively associated with cannabis use in both men and women. Evaluation of the role of stress and trauma in cannabis use and related gender differences deserve further attention. Endocannabinoid system dysregulation may explain why trauma exposed individuals have high rates of cannabis use.